The Role of Clinical Supervision: Teaching Basic Obstetric Ultrasound for Undergraduate Medical Students - Herlambang Herlambang; Amelia Dwi Fitri; Nyimas Natasha Ayu Shafira; Anggelia Puspasari; Susan Tarawifa (Universitas Jambi, Indonesia, 2020)
This study aimed to find the impact of clinical supervision on the achievement of medical student competence in basic obstetric ultrasound examination skills by using DOPS as the assessment method. Students’ knowledge related to basic obstetric ultrasound examination in the beginning and in the end of their 10 weeks clinical rotation in Department of Obstetrics and Gynecology were assessed by using pre-test and post-test questionnaire. By employing mixed methods, one group pre and post-test design was positioned to assess student knowledge, one group post-test design to assess student’s skills achievement and qualitative study to explore student perception about the new learning method we offered. The collected data were analyzed with computer program; means and standard deviation were calculated as descriptive parameters. Parametric test were used to test the hypothesis. The pre-post results were compared by using Wilcoxon test. The results showed a significant difference in the score of pre-test and post-test. Qualitative data showed positive perception. Clinical supervision as teaching method together with learning media in the form of module and ultrasound video gave positive result to improve achievement of student’s competence in basic obstetric ultrasound examination skills.